In silico studies of isatinyl-2-aminobenzoylhydrazone transition metal complexes against cyclin-dependent kinase 6 (CDK6) - Nusantoro, Yesaya Reformyada; Fadlan, Arif (Pharmacy Reports, 2021)
Cyclin-dependent kinase 6 (CDK6) is an important member of protein kinases, involving in many cellular pathways especialy cell cycle progression. Thus, CDK6 is a promising target in cancer therapy. This report aims to predict inhibiton of CDK6 by some complex compounds by using molecular docking and pharmacological properties analysis. Those compounds are isatinyl-2-aminobenzoylhydrazone (ISABH) and cobalt (II), nickel (II), copper (II), and zinc (II) transition metal complexes. The molecular docking against CDK6 (PDB code: 3NUP) revealed that ISABH/ISABH-transition metal complexes established ligand-protein interaction as expressed by negative binding affinity values. Drug-likeness by SwissADME indicated that ISABH and Ni-ISABH met the Lipinski’s rule of five. Both compounds also showed reasonable pharmacological criteria by admetSAR.